Teaching excellence? : universities in an age of student consumerism - Gunn, Andrew (Andrew Steven); Gunn, Andrew (London : SAGE Publications Ltd, 2023)
This new title explores the role of teaching within the modern university and the impact of the Teaching Excellence and Student Outcomes Framework (TEF). It provides a critical analysis of recent policy reforms designed to increase competition and choice in higher education and what these mean for the sector. It also surveys the wider landscape and the rise of the student as consumer within HE.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Education, Higher -- Administration; Education, Higher -- Law and legislation